Filter media and uses thereof

By introducing beads distributed along the elongation direction of the nanofiber filter media, the problem of the nanofiber filter media being easily contaminated during use and causing an increase in pressure loss, achieving the effects of low pressure loss, high capture efficiency and high dust capacity.

CN119869091APending Publication Date: 2025-04-25TORAY FIBER RES INST(CHINA) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311387766.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

Smart Images

  • Figure CN119869091A_ABST
    Figure CN119869091A_ABST
Patent Text Reader

Abstract

The invention discloses a filter medium and application thereof, the filter medium at least comprises a base material layer and a nanofiber web layer, the nanofiber web layer contains nanofibers and beads distributed along the extension direction of the nanofibers, the average diameter of the beads is 25-100 times of the average diameter of the nanofibers, and the distribution quantity of the beads is 30-400 / mm < 2 >. The filtering medium disclosed by the invention has the characteristics of low pressure loss, high trapping efficiency and high dust holding capacity, and can be applied to an air filter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a filter medium and use thereof. Background Art

[0002] In recent years, due to the characteristics of nanofiber membranes such as high specific surface area, high surface activity, and high surface cohesive energy, which determine their high adsorption performance, the filter media made of nanofiber membranes have the advantages of high capture efficiency and low pressure loss. Therefore, nanofiber materials are increasingly widely used in the field of filtration.

[0003] However, conventional nanofibers do not have beads in their elongation direction. Therefore, although the filter material made from them has a high filtration efficiency in the initial stage of use, due to the fine nanofibers and small pores in the nanofiber layer, as the use time increases, the nanofiber layer in the filter material is easily covered by particulate pollutants and oil in the air, forming a dense oil layer, which causes the pressure loss of the filter material to increase sharply and the service life to decrease.

[0004] For example, Chinese patent CN115006917A discloses a fluffy nano-filter material. As is well known, compared with ordinary fibers, nano-fibers have extremely high aspect ratios and electrostatic attraction, and fibers are easily bonded together. After a period of use, the filter material formed by the nano-fiber layer is difficult to maintain its fluffy state. An oil film will form on the nano-fiber layer, blocking the pores between the fibers, resulting in a decrease in the filtering effect of the filter material and a shortened service life.

[0005] In order to solve the problem that the nanofiber layer is easily blocked, resulting in low filtering effect of the filter material, technicians have developed a nanofiltration medium containing nano beads. For example, Chinese patent CN208878073U discloses a nano material and a filter medium, which includes a substrate layer and a nanofiber layer, wherein the nanofiber layer includes a plurality of nanofibers and a plurality of beads. Although the beads can support the nanofibers to prevent the pores between the fibers from collapsing, if there are too few beads, the supporting effect is small; but if there are too many beads, the pores between the nanofibers and the beads are too large, which will block the pores between the nanofibers, thereby causing a sharp increase in the pressure loss of the filter medium and a reduction in the service life. Summary of the invention

[0006] The object of the present invention is to provide a filter medium with low pressure loss, high collection efficiency and high dust holding capacity.

[0007] The technical solution of the present invention is as follows: the filter medium of the present invention comprises at least a substrate layer and a nanofiber web layer, wherein the nanofiber web layer contains nanofibers and beads distributed along the elongation direction of the nanofibers, wherein the average diameter of the beads is 25 to 100 times the average diameter of the nanofibers, and the distribution amount of the beads is 30 to 400 per mm 2 .

[0008] Beneficial effects of the present invention: The filter medium of the present invention can not only effectively filter pollutants in the air, but also remain fluffy after being used for a long time. It has the characteristics of low pressure loss, high capture efficiency and high dust holding capacity, and can be applied to air filters. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is an electron scanning image of the nanofiber web layer in the filter medium, where a is nanofiber and b is beads distributed along the elongation direction of the nanofiber. DETAILED DESCRIPTION

[0010] The filter medium of the present invention comprises at least a substrate layer and a nanofiber web layer, wherein the nanofiber web layer contains nanofibers and beads distributed along the elongation direction of the nanofibers, wherein the average diameter of the beads is 25 to 100 times the average diameter of the nanofibers, and the distribution amount of the beads is 30 to 400 per mm 2 . The above-mentioned substrate layer mainly plays a supporting role. Since the nanofiber has a large aspect ratio α (α>1000) and the diameter of the fiber is very fine, the prepared nanofiber mesh layer will be very soft, which is easy to cause deformation of the material under a certain air volume, thereby reducing the service life of the filter medium. Therefore, the nanofiber mesh layer needs to be supported by a substrate with a rigid effect. The substrate is preferably one or more of wet papermaking non-woven fabrics, thermal bonding non-woven fabrics, spunbond non-woven fabrics, and meltblown non-woven fabrics, but is not limited to the above forms. The substrate layer can be a single-layer structure, which not only plays a supporting role, but also plays a role in primary filtration, filtering out some large particles of dust; it can also be a multi-layer structure. When the substrate layer is a multi-layer structure, the nanofiber mesh layer is arranged in the middle of the multi-layer substrate layer, which can protect the nanofiber mesh layer from being damaged during the later processing processes such as pleating.

[0011] The nanofiber web of the present invention can be prepared by an island-in-sea composite spinning method or by a polymer jet electrostatic stretch spinning method. Among them, by controlling the parameters of melt spinning on the spinning machine in the island-in-sea composite spinning method and by controlling the processing conditions of the electrostatic spray equipment in the polymer jet electrostatic stretch spinning method, beads will be distributed along the elongation direction of the nanofibers. If the island-in-sea composite spinning method is adopted, the fiber web obtained by laying and reinforcement needs to be alkali-reduced to finally obtain a nanofiber web layer. The process is complicated, and the fibers of the nanofiber web layer are easily entangled and damaged during the alkali reduction treatment, which reduces its filtering characteristics. It is difficult to obtain a nanofiber web with higher performance using the existing technology. If the polymer jet electrostatic stretch spinning method is adopted, it is preferred because the method has the advantages of simple operation, wide application range, and high production efficiency.

[0012] Beads are distributed along the elongation direction of the nanofibers, and the average diameter of the beads is 25 to 100 times the average diameter of the nanofibers. Since the nanofibers have an extremely high aspect ratio and electrostatic attraction, the fibers are easily tightly bonded together, thereby reducing the specific surface area between the fibers, which will reduce the probability of collision between pollutant particles and bacteria, virus-like substances and the fibers, resulting in a decrease in the capture efficiency of the filter material. However, when a certain number of beads are distributed in the elongation direction of the nanofibers, the presence of the beads can increase the distance between the fibers, so that the electrostatic attraction force between the fibers is relatively weakened, forming a unique spatial mesh structure inside the nanofiber net, thereby improving the bulkiness of the overall structure of the fiber net. In addition, when the filter medium of the present invention captures pollutant particles, the particles pass through the unique spatial mesh structure. Since the structure is equivalent to having a lot of curved aperture channels, the time for pollutant particles to pass through the filter medium will be extended, thereby improving the capture efficiency of the filter medium. When the ratio of the bead diameter to the average diameter of the nanofiber is less than 25, the distance between the nanofibers cannot overcome their own electrostatic attraction, and the fibers are still easy to stick together. The overall structure of the nanofiber network is compact and easy to clog; when the ratio of the bead diameter to the average diameter of the nanofiber is greater than 100, the overly large beads on the nanofiber network will not form a unique spatial network structure inside the nanofiber network, but will form larger pores, thereby causing pollutant particles and bacteria and viruses to be released through the larger pores, and ultimately fail to play a filtering role. Therefore, considering that the filter medium has a higher capture efficiency, the average diameter of the beads is preferably 40 to 80 times the average diameter of the nanofibers.

[0013] The distribution of the above beads is 30 to 400 / mm 2The distribution of beads includes the inside and outside of the nanofiber net. The presence of beads can reduce the packing density between nanofibers, increase the fluffiness of the nanofiber net, and help improve the capture efficiency of the filter medium. At the same time, due to the molecular slip effect between the nanofiber and bead structure, the pressure loss of the filter medium can be significantly reduced. When the distribution of beads is less than 30 / mm 2 When the nanofibers and beads are too small to form a unique spatial network structure, the overall fluffiness of the fiber network structure is still poor. After long-term use, pollutants are easily deposited on the surface and inside of the filter medium, forming an oil film layer, which leads to a sharp increase in the pressure loss of the filter medium, a gradual decrease in the capture efficiency, and a shortened service life of the filter material. When the distribution of beads is greater than 400 / mm 2 Although the fluffiness of the nanofiber web will be significantly improved, the presence of too many beads in the elongation direction of the nanofibers will not only increase the pores of the fiber web layer, but also release pollutant particles, bacteria, and viruses through the pores, thereby reducing the capture efficiency of the filter medium. In addition, too many beads can easily block the pores inside the fiber web, resulting in increased pressure loss of the filter medium and reduced service life. Therefore, considering the balance between pressure loss, capture efficiency, and service life of the filter medium, the distribution amount of beads is preferably 100 to 300 beads / mm 2 .

[0014] The average diameter of the above-mentioned nanofibers is preferably 100 to 800 nm. The nanofiber mesh layer of the present invention mainly plays a filtering role, capturing and blocking fine particles in the air through nano-electrostatic adsorption. When it is too small, due to the excessively fine fiber diameter, the fibers will be too close to each other, so the pores between the fibers will become smaller. Although pollutant particles in the air and bacteria and viruses can be captured, these substances will soon fill the tight fiber mesh, resulting in a sharp increase in the pressure loss of the filter medium and a decrease in service life; when it is too large, due to the excessively thick diameter of the nanofibers, the distance between the fibers will become larger, and the pore size of the nanofiber mesh will also increase, making it difficult to capture particles with smaller particle sizes, resulting in a decrease in the capture efficiency of the filter medium. Therefore, considering the balance between the pressure loss, capture efficiency and service life of the filter medium, the average diameter of the nanofibers is more preferably 200 to 600 nm.

[0015] The coefficient of variation of the bead diameter in the filter medium of the present invention is preferably above 80%. The coefficient of variation is an absolute value used to measure the degree of data dispersion. The coefficient of variation of the bead diameter in the filter medium of the present invention reflects the fluctuation of the bead diameter. The larger the coefficient of variation of the bead diameter, the larger the ratio of the standard deviation of the bead diameter to the average diameter of the bead. At this time, the uniformity of the average diameter of the bead will be relatively reduced, so the pore size caused by the beads will present a form of different sizes. Therefore, the fluffiness of the formed nanofiber net will be relatively good, with a unique spatial mesh structure. During use, the prepared filter medium first performs surface filtration on the captured particulate pollutants and bacteria and virus substances in the air, and then slowly enters the internal tortuous mesh pores, thereby improving the capture efficiency of the filter medium, reducing pressure loss, and extending the service life. Therefore, considering that the fluffiness of the nanofiber net layer will have a beneficial effect on the capture efficiency and service life of the filter medium, the coefficient of variation of the bead diameter is more preferably above 100%.

[0016] The average pore size of the pores of the fiber mesh formed between the nanofibers and beads of the present invention is preferably 1 to 100 μm. The average pore size of the fiber mesh pores here refers to the size of the average pore size formed by the pores between nanofibers, between nanofibers and beads, and between beads. The size of the average pore size directly affects the filtering level of the filter medium for particulate pollutants and bacteria and viruses in the air. The larger the average pore size, the easier it is for particulate pollutants and bacteria and viruses in the air to flow out of the pores and the more difficult it is to be captured, so the capture efficiency of the filter medium is lower. Conversely, the smaller the average pore size, the greater the probability of the above substances being captured. Therefore, considering the capture efficiency of the filter medium for particulate pollutants and bacteria and viruses in the air, the average pore size of the pores of the fiber mesh formed between nanofibers and beads is more preferably 5 to 80 μm.

[0017] The nanofibers of the present invention are preferably polyurethane, polyvinylidene fluoride, polysulfone, polyethersulfone, polyamide, polystyrene, polyacrylonitrile, polylactic acid or cellulose diacetate. Under the premise of ensuring that the nanofiber net in the filter medium has excellent mechanical properties, heat resistance, corrosion resistance, etc., the nanofibers of the present invention are more preferably polyurethane fibers, polyvinylidene fluoride fibers or polyamide 6 fibers. Polyurethane fibers have good elasticity, good mechanical properties, small compression deformation, and also have excellent chemical resistance, heat insulation, sound insulation, shock resistance, and anti-toxicity; polyvinylidene fluoride fibers have excellent mechanical strength, toughness, mildew resistance, and wear resistance; polyamide 6 fibers have excellent mechanical strength, toughness, heat resistance, fatigue resistance, and corrosion resistance.

[0018] The present invention is further described by the following examples, but the protection scope of the present invention is not limited to the examples. The physical property parameters in the examples are measured by the following methods.

[0019]

Average diameter of nanofibers

[0020] The filter medium with a size of about 1.0cm×1.0cm was peeled off, and the nanofiber mesh layer was used as the shooting surface. It was then photographed using an SS-550 scanning electron microscope (SEM) produced by Shimadzu Corporation with a shooting magnification of 500 times. The diameter of the nanofibers in the nanofiber mesh layer was then randomly measured using software. 100 sets of data were measured and the average value was calculated, which was the average diameter of the nanofibers.

[0021] [Average diameter of beads]

[0022] The filter medium with a size of about 1.0cm×1.0cm was peeled off, and the nanofiber mesh layer was used as the shooting surface. It was then photographed using an SS-550 scanning electron microscope (SEM) produced by Shimadzu Corporation with a shooting magnification of 500 times. The diameter of the beads in the nanofiber mesh layer along the elongation direction of the nanofibers was randomly measured using software. 100 sets of data were measured and the average value was calculated, which was the average diameter S1 of the beads.

[0023]

Coefficient of variation of bead diameter

[0024] The coefficient of variation of bead diameter refers to the ratio of the standard deviation of bead diameter to the average diameter of the beads, in %. The standard deviation of bead diameter is calculated by the above-mentioned "average diameter of beads" test method, and its calculation formula is: standard deviation S2 = ∑ (Si-S1)^2 / (n-1)^2, where Si is the diameter of each group of beads; n = 100, representing the number of diameter test data. Then the coefficient of variation of bead diameter is calculated by the following calculation formula: coefficient of variation (%) = S2 / S1×100%.

[0025]

Distribution amount of beads

[0026] The filter medium with a size of about 1.0cm×1.0cm was peeled off, and the nanofiber mesh layer was used as the shooting surface. Then it was photographed by SS-550 scanning electron microscope (SEM) produced by Shimadzu Corporation. The shooting magnification was 500 times. After the test unit area was randomly determined by the software, the number of beads was measured by the software. After 50 groups of measurement data, the average value was taken, and the average value was the distribution amount of the beads.

[0027]

Average pore size

[0028] The filter medium with a size of about 1.0cm×1.0cm was peeled off to obtain a nanofiber mesh layer. The nanofiber mesh was then made into a circle with a diameter of 1.5cm. After being soaked in PMI surface tension special test liquid Galwick for 30 minutes, the sample was placed face up in the test slot of the capillary flow pore tester. After tightening the slot cover, the test was carried out. The pore size distribution (μm) in the nanofiber mesh layer was calculated by software, and the average value of the data measured 10 times was taken as the average pore size.

[0029]

Collection efficiency

[0030] With reference to JIS B 9908 standard, according to the filter medium collection efficiency test method specified therein, 5 points were randomly selected to measure the collection efficiency of the filter medium and the average value was calculated.

[0031]

Pressure loss

[0032] Referring to the JIS B 9908 standard, according to the filter medium pressure loss test method specified therein, 5 points were randomly selected to measure the filter medium pressure loss and the average value was calculated.

[0033]

Dust volume

[0034] According to ISO-11155 standard, A2 dust is used as the test particle, and the air volume is 117m 3 / h, add dust to the tested filter medium until the pressure loss reaches 200 Pa. The ratio of the amount of dust added to the area of ​​the filter medium is the dust capacity. The larger the dust capacity, the longer the service life of the filter medium.

[0035] Example 1

[0036] The polyester fiber is combed into a web and heat-bonded to obtain a polyester heat-bonded non-woven fabric, and the polyurethane polymer is used as a raw material for electrostatic spinning, and sprayed on one side of the substrate layer by an electrostatic spray device for deposition to obtain a composite material containing a nanofiber mesh layer, that is, the filter medium of the present invention is obtained. The average diameter of the nanofibers in the nanofiber mesh layer of the filter medium is measured to be 500nm, and the average diameter of the beads distributed along the elongation direction of the nanofibers is 25μm, and the distribution amount of the beads is 223 / mm 2 The coefficient of variation of the bead diameter is 110%. The physical properties of the filter medium of the present invention are shown in Table 1.

[0037] Embodiment 2-3

[0038] The preparation process is the same as in Example 1, and the specific formula and physical properties are shown in Table 1.

[0039] Example 4

[0040] First, the polyester fibers are combed into a web and heat-bonded to obtain a polyester heat-bonded non-woven fabric. The polyurethane high molecular polymer is used as the raw material for electrostatic spinning, and the polyurethane is sprayed on one side of the substrate layer through an electrostatic spray device for deposition to obtain a composite material containing a nanofiber mesh layer. The polyester slices are then spun, stretched, and the filaments are laid and reinforced to obtain a polyester spunbond non-woven fabric. The spunbond non-woven fabric, the nanofiber mesh layer, and the heat-bonded non-woven fabric are then composite-processed in a top-down order to obtain the filter medium of the present invention. It was measured that the average diameter of the nanofibers in the nanofiber mesh layer in the filter medium is 500nm, and the average diameter of the beads distributed along the elongation direction of the nanofibers is 25μm, and the distribution amount of the beads is 186 / mm 2 The coefficient of variation of the bead diameter is 85%. The physical properties of the filter medium of the present invention are shown in Table 1.

[0041] Embodiment 5, 9

[0042] The preparation process is the same as that of Example 4, and the specific formula and physical properties are shown in Table 1.

[0043] Embodiments 6 to 8 and 10

[0044] The preparation process is the same as in Example 1, and the specific formula and physical properties are shown in Table 1.

[0045] Embodiment 11

[0046] The polyester fibers are combed into a web and heat-bonded to obtain a polyester heat-bonded nonwoven fabric. The polyurethane polymer is used as the raw material for island-type multi-component spinning. The polyurethane nanofiber raw material is used as the island component and the alkali-reduced polyester polymer is used as the sea component. The island weight is 7:3 and melt-spun on a spinning machine. After stretching, the island-island composite filaments are obtained. After the web is laid and heat-cured, the obtained island-island composite fiber web is subjected to alkali reduction to obtain a nanofiber web layer. The polyester heat-bonded nonwoven fabric and the nanofiber web layer are then composite-processed to obtain the filter medium of the present invention. It was measured that the average diameter of the nanofibers in the nanofiber web layer of the filter medium is 500nm, and the average diameter of the beads distributed along the elongation direction of the nanofibers is 25μm. The distribution amount of the beads is 226 / mm 2 The coefficient of variation of the bead diameter is 110%. The physical properties of the filter medium of the present invention are shown in Table 1.

[0047] Comparative Example 1

[0048] The polyester fiber is combed into a web and heat-bonded to obtain a polyester heat-bonded non-woven fabric, and the polyurethane polymer is used as a raw material for electrostatic spinning, and sprayed on one side of the substrate layer by an electrostatic spray device for deposition to obtain a composite material containing a nanofiber web layer, that is, the filter medium of the present invention is obtained. It is measured that the average diameter of the nanofibers in the nanofiber web layer is 500nm, and beads with an average diameter of 60μm are distributed along the elongation direction of the nanofibers, and the distribution amount of the beads is 223 / mm 2 The coefficient of variation of the bead diameter is 85%. The physical properties of the filter medium are shown in Table 2.

[0049] Comparative Examples 2 to 4

[0050] The preparation process is the same as that of Comparative Example 1, and the specific formula and physical properties are shown in Table 2.

[0051] Table 1

[0052]

[0053] Table 2

[0054]

[0055] According to the above table,

[0056] (1) It can be seen from Examples 1, 2 and 8 that, under the same conditions, the ratio of the average diameter of the beads to the average diameter of the nanofibers in Example 1 is within a preferred range, and the filter medium obtained has a smaller pressure loss, a higher collection efficiency and a higher dust volume, that is, the service life of the filter medium is longer. (2) It can be seen from Examples 1 and 3 that, under the same conditions, the coefficient of variation of the bead diameter in Example 1 is within a more preferred range. Compared with the latter, the filter medium obtained by the former has a smaller pressure loss, a higher collection efficiency and a higher dust volume, that is, the service life of the filter medium is longer.

[0057] (3) It can be seen from Examples 4, 5 and 9 that, under the same conditions, the distribution amount of the beads in Example 4 is within the preferred range, the pressure loss of the obtained filter medium is smaller, and the dust volume is higher.

[0058] (4) It can be seen from Example 1 and Example 6 that, under the same conditions, the average diameter of the nanofibers in the former is within a more preferred range, and compared with the latter, the filter medium obtained in the former has higher capture efficiency and dust volume.

[0059] (5) It can be seen from Example 1 and Example 7 that, under the same conditions, the average pore size of the nanofiber mesh in Example 1 is within a more preferred range, and the resulting filter medium has a small pressure loss, a high collection efficiency and a high dust holding capacity, that is, the service life of the filter medium is long.

[0060] (6) It can be seen from Example 1 and Example 10 that, under the same conditions, the coefficient of variation of the bead diameter in the latter is not within the preferred range, that is, the coefficient of variation of the bead diameter is small, and the pressure loss of the filter medium obtained by the latter is slightly higher, and the capture efficiency and dust volume are slightly lower.

[0061] (7) It can be seen from Example 1 and Example 11 that, under the same conditions, the former adopts the polymer jet electrostatic stretching spinning method, and the latter adopts the island-type multi-component spinning method. The filter medium made of the nanofiber mesh layer in the former has a small pressure loss, a high capture efficiency and a high dust volume, that is, the service life of the filter medium is long.

[0062] (8) It can be seen from Example 1 and Comparative Examples 1 and 2 that, under the same conditions, the ratio of the average diameter of the beads to the average diameter of the nanofibers in Comparative Examples 1 and 2 is too large or too small, and the resulting filter medium has a high pressure loss and a low dust volume, that is, the service life of the filter medium is short.

[0063] (9) It can be seen from Example 1 and Comparative Examples 3 and 4 that, under the same conditions, the distribution amount of beads in Comparative Examples 3 and 4 is too much or too little, and the resulting filter medium has low capture efficiency and low dust volume, that is, the service life of the filter medium is short.

Claims

1. A filter medium, characterized in that: The filter medium at least comprises a substrate layer and a nanofiber web layer, wherein the nanofiber web layer contains nanofibers and beads distributed along the elongation direction of the nanofibers, wherein the average diameter of the beads is 25 to 100 times the average diameter of the nanofibers, and the distribution amount of the beads is 30 to 400 per mm 2 .

2. The filter medium according to claim 1, characterized in that: The average diameter of the nanofibers is 100-800 nm.

3. The filter medium according to claim 1, characterized in that: The coefficient of variation of the bead diameter is greater than 80%.

4. The filter medium according to claim 1, characterized in that: The distribution amount of the beads is 100 to 300 per mm 2 .

5. The filter medium according to claim 1, characterized in that: The average pore size of the pores in the fiber network formed between the nanofibers and the beads is 1 to 100 μm.

6. The filter medium according to claim 1, characterized in that: The nanofiber is polyurethane, polyvinylidene fluoride, polysulfone, polyethersulfone, polyamide, polystyrene, polyacrylonitrile, polylactic acid or cellulose diacetate fiber.

7. Use of the filter medium according to claim 1 in an air filter.

Citation Information

Patent Citations

  • Fluffy nano filter material as well as preparation method and application thereof

    CN115006917A

  • The invention discloses a nano material and a filtering medium

    CN208878073U